Vertically Resolved Magma Ocean–Protoatmosphere Evolution: H2, H2O, CO2, CH4, CO, O2, and N2 as Primary Absorbers. Issue 2 (23rd February 2021) - Lichtenberg, Tim; Bower, Dan J.; Hammond, Mark; Boukrouche, Ryan; Sanan, Patrick; Tsai, Shang‐Min; Pierrehumbert, Raymond T.
Abstract: The earliest atmospheres of rocky planets originate from extensive volatile release during magma ocean epochs that occur during assembly of the planet. These establish the initial distribution of the major volatile elements between different chemical reservoirs that subsequently evolve via geological cycles. Current theoretical techniques are limited in exploring the anticipated range of compositional and thermal scenarios of early planetary evolution, even though these are of prime importance to aid astronomical inferences on the environmental context and geological history of extrasolar planets. Here, we present a coupled numerical framework that links an evolutionary, vertically resolved model of the planetary silicate mantle with a radiative‐convective model of the atmosphere. Using this method, we investigate the early evolution of idealized Earth‐sized rocky planets with end‐member, clear‐sky atmospheres dominated by either H2, H2 O, CO2, CH4, CO, O2, or N2 . We find central metrics of early planetary evolution, such as energy gradient, sequence of mantle solidification, surface pressure, or vertical stratification of the atmosphere, to be intimately controlled by the dominant volatile and outgassing history of the planet. Thermal sequences fall into three general classes with increasing cooling timescale: CO, N2, and O2 with minimal effect, H2 O, CO2, and CH4 with intermediate influence, and H2 with several orders of magnitude increase in solidification time and atmosphere vertical stratification. Our numerical experiments exemplify the capabilities of the presented modeling framework and link the interior and atmospheric evolution of rocky exoplanets with multiwavelength astronomical observations. Plain Language Summary: The climate and surface conditions of rocky planets are sensitive to the composition of their atmospheres, but the origins of these atmospheres remain unknown. During the final stages of planetary accretion, when the whole of the planet solidifies from lava to solid rock, volatiles can rapidly cycle between interior and atmosphere, and control the cooling properties of the planet. In order to understand how cooling planets with different volatile compositions evolve, we use computer simulations to analyze their thermal evolution, outgassing, and observable signatures. We find the planetary cooling sequence to differ by orders of magnitude depending on the primary volatile. CO, N2, and O2 rapidly outgas, but allow planets to solidify efficiently. H2 O, CO2, and CH4 build an intermediate class with substantially delayed cooling, but varying outgassing rate. H2 most efficiently inhibits solidification relative to the other cases. All considered volatiles show distinctive evolution of the atmosphere and interior and display different atmospheric signals that can be measured by astronomical surveys. Deviations in the geological properties of the planetary interior similarly manifest in the atmospheric signal. Future observations may isolate distinctive features in exoplanet atmospheres to infer interior state and composition. Key Points: Magma oceans with different volatiles display varying timescales of solidification, outgassing, and atmospheric stratification Atmospheric blanketing and cooling time increase in three principle classes from N2, CO, O2 to H2 O, CO2, CH4 to H2 Coupled mantle–atmosphere systems display distinctive features that link the interior and surface state to atmospheric spectrum and climate